Developing e-learning-based remedial learning videos on function for senior high schools - Johar, Rahmah; Rizeky, Amna Sri; Mailizar (Universitas Papua, 2024)
Mastery learning remains a critical challenge in education, often resulting in the need for remedial programs to support students in achieving competency. Despite their importance, existing remedial programs frequently fail to achieve their intended outcomes due to a lack of engaging and efficient instructional tools. To address this gap, this study introduces a novel e-learning-based remedial video designed to enhance student learning on the topic of functions. The research aimed to develop a remedial learning video that meets the criteria for validity, practicality, and effectiveness. The study employed a Research and Development (R&D) methodology following the Plomp model, which consists of three phases: preliminary research, prototyping, and assessment. The research was conducted in a high school in Banda Aceh, Indonesia, involving three distinct groups: nine students participated in the readability test, 60 students undertook the diagnostic test, and 18 students engaged in remedial learning activities. Data collection utilized validation sheets for the video, diagnostic and remedial tests, and student response questionnaires, with descriptive analysis applied to evaluate the findings. The results revealed that the e-learning-based remedial video demonstrated strong validity, with expert assessments yielding a score of 86.19% (very valid). Practicality was confirmed by positive student feedback, with a response rate of 92.62%. Effectiveness was also evident, as 95% of students achieved mastery learning following the remedial intervention, and the N-Gain score reflecting improvement in student performance was 0.72 (high). These outcomes underscore the effectiveness of e-learning-based remedial videos as an innovative and interactive solution to address students' lack of mastery learning. The findings contribute to educational practice by offering teachers and students an accessible and effective tool to enhance learning outcomes, with significant potential for broader application.